Proportional sway-based electrotactile feedback improves lateral standing balance - Raghav Hari Krishna, V. S.; Kim, Jeonghee; Chang, Shuo-Hsiu; Choe, Yoonsuck; Park, Hangue (Frontiers in Neuroscience, 2024)
Introduction Plantar cutaneous augmentation is a promising approach in balance rehabilitation by enhancing motion-dependent sensory feedback. The effect of plantar cutaneous augmentation on balance has been mainly investigated in its passive form (e.g., textured insole) or on lower-limb amputees. In this study, we tested the effect of plantar cutaneous augmentation on balance in its active form (i.e., electrical stimulation) for individuals with intact limbs. Methods Ten healthy subjects participated in the study and were instructed to maintain their balance as long as possible on the balance board, with or without electrotactile feedback evoked on the medial side of the heel, synched with the lateral board sway. Electrotactile feedback was given in two different modes: 1) Discrete-mode E-stim as the stimulation on/off by a predefined threshold of lateral board sway and 2) Proportional-mode E-stim as the stimulation frequency proportional to the amount of lateral board sway. All subjects were distracted from the balancing task by the n-back counting task, to test subjects’ balancing capability with minimal cognitive involvement. Results Proportional-mode E-stim, along with the n-back counting task, increased the balance time from 1.86 ± 0.03 s to 1.98 ± 0.04 s (p = 0.010). However, discrete-mode E-stim did not change the balance time (p = 0.669). Proportional-mode E-stim also increased the time duration per each swayed state (p = 0.035) while discrete-mode E-stim did not (p = 0.053). Discussion These results suggest that proportional-mode E-stim is more effective than discrete-mode E-stim on improving standing balance. It is perhaps because the proportional electrotactile feedback better mimics the natural tactile sensation of foot pressure than its discrete counterpart.